(untitled) (Journal for Studies in Humanities and Social Sciences, 2014)
Malaria is on the decline in Namibia due to interventions by the Ministry of Health and Social Services (MoHSS) and the country is moving towards pre-elimination of the disease. However, barriers such as resistance of the uptake of interventions by "at risk" communities, e.g. lack of treatment seeking behavior for WHO recommended ACT’s exist. Some communities in malaria-endemic areas do not accept Western medicine, preferring traditional medicines as prescribed by traditional healers. It is important to balance people’s cultural beliefs and practices with the MoHSS’s objective of malaria elimination by 2020. To facilitate integration of traditional treatments into mainstream malaria case management, documentation and validation of the treatments to allow their safe and effective use have to be carried out. This study was conducted to document and validate the use of seven plants native to Namibia, targeted on the basis of their indigenous uses which suggest their toxicity to Plasmodium parasites. Crude extracts were prepared using methanol-dichloromethane (1/1V/V) and distilled water at 60 C. The extracts were further Partitioned with chloroform-methanol water (12/6/lV/V). Preliminary phytochemical screening was performed to detect the presence of selected Antiplasmodial compounds. Phytochemical tests revealed the presence of anthraquinones, flavonoids, terpenoids, coumarines, and glycosides; alkaloids and steroids were not detected. Paradoxically, thin-layer chromatography analysis on the crude extracts of the same plants tested positive for all compounds. The presence of these phytochemicals and the data generated support the ethno-medicinal uses for these plants